Analisis Optimasi Aplikasi Sistem Irigasi Tetes PVC Ber-Amiter pada Variasi Lahan Bertingkat Untuk Mendukung Kegiatan Pertanian di Permukiman Perkotaan: Optimization Analysis of the Application of Emitter PVC Drip Irrigation Systems on Variations of Multistorey Land to Support Agricultural Activities in Urban Settlements - I Dewa Gede Jaya Negara; Lilik Hanifah; Anid Supriyadi; Eko Pradjoko; Atas Pracoyo (LPPM Universitas Mataram, 2023)
Multilevel drip irrigation with PVC pipes is an efficient irrigation method that has the potential to be applied in urban settlements. Even though the land used is not very large, farming can be done effectively because it uses polybag land. This study aims to determine the effect of variations in PVC pipe drip irrigation networks with amiter on irrigation distribution, irrigation uniformity, and soil moisture levels with variations in irrigation duration. The test was carried out on four variations of tower water level and four variations of PVC drip irrigation networks in a multi-level system, with four variations of irrigation duration t1=5 minutes, t2=10 minutes, t3=15 minutes and t4=20 minutes. The test data analyzed includes irrigation distribution data and irrigation uniformity (Cu) and soil moisture recharge (Wt). The analysis results show that the best distribution of drip irrigation is obtained in network variation 3 with an average of 69 ml. The average uniformity obtained for Cu is above 97%, which is considered very good. Soil moisture Wt in variation 3 drip irrigation networks for a depth of 20 cm ranges from 0.69% - 21.65% at L1, at L2 around 2.16% - 21.65%, at L3 is 2.19% -21.68 % and at L4 it is 10.41% - 28.66%, so the higher the level position, the greater the soil moisture addition provided by irrigation.